PROTECTED ENVIRONMENTS AND REFLECTIVE MATERIAL IN THE PRODUCTION OF Hymenaea courbaril SEEDLINGS - di Matheus e Souza, Vitória Cristina; da Silva, Abimael Gomes [UNESP]; Costa, Edilson; da Silva Binotti, Flávio Ferreira; da Costa Vieira, Gustavo Haralampidou (Universidade Federal do Paraná, 2022)
Most seedling production is carried out in protected environments influencing plant growth and development. The present study aimed to evaluate types of the cover of protected environments and reflective material in the production of seedlings of Hymenaea courbaril. The experiments were carried out in four protected environments: (A1) agricultural greenhouse covered with low-density polyethylene (LDPE) film with 42% - 50% shading screen under the film; (A2) agricultural screen with an aluminized screen with 35% shading; (A3) agricultural screen with a black screen of 30% of shading, and (A4) agricultural screen with a black screen of 18% of shading. Production systems were tested with and without reflective material on the cultivation bench in each protected environment. The photosynthetically active radiation reflecting material used was the aluminized screen (Aluminet®). As there were no repetitions of the protected environments, each environment was considered an experiment. In each environment, the experimental design used was completely randomized, with four replications and five plants per plot. Among the variables analyzed, it was observed that the agricultural screen with a black screen (18% of shading) presented better quality seedlings. The system with reflective material presented higher values of the number of leaves and stem diameter.
Ambientes protegidos e material refletor na produção de mudas de Hymenaea courbaril
Keywords: Aluminum screen; Black screens; Jatobazeiro; Ldpe film